"Always Ambitious of Having Me Appear to Advantage": Renouncing Fashion in Georgiana Cavendish's Emma; or, The Unfortunate Attachment and The Sylph. Issue 3 (3rd July 2022) - Schoppe, Ashley
ABSTRACT: This article aims to recover the novels of Georgiana Cavendish, Fifth Duchess of Devonshire, and to shed light on the narrative her fiction offers regarding women's imagined susceptibility to fashion. Analysing the treatment of fashion in her two novels, Emma; or, the Unfortunate Attachment (1773) and The Sylph (1778), and particularly the female protagonists' rejection of stylish clothing, I argue that Cavendish is not simply replicating the late eighteenth-century trend of associating virtue with a renunciation of fashion. Rather, her novels strive to reverse gender stereotypes that position women as vain and obsessed with dress by revealing that it is men who benefit from the adorned female body while women function merely as symbols of the aristocratic family's social status and wealth.